Scientific Learning on the Teaching with Theme Always Save the Energy - Novelasari, Setia Asri; Wardani, Sri; Sunarso, Ali (Journal of Primary Education, 2020)
The objective of this research is to analyze the observation activity, to ask, to try, to analyze, and to communicate with the theme Always Save the Energy using scientific learning approach in elementary school. This is qualitative research. The object was purposively in SDN 4 Penyangkringan Kecamatan Weleri Kabupaten Kendal. Data collection was taken by observation, interview, and documentation. Data analysis was done by data reduction, data display, and conclusion. Triangulation was done to get the data validity. The result of the research shows that the scientific approach in the Always Save the Energy theme uses observation, asking the question, and collecting information in the learning activity. The observation activity done by the student is observing pictures in books and LCD, observing video prepared by the teacher, observing the realia, and observing the teacher’s explanation. The asking activity is; asking and giving answers between teachers and students after they observed and listened to the teacher’s explanation. The experiment activity was in the group, to prove about the evaporation liquid by sunlight, practicing a song notation, corn planting, making windmill from used drinking bottle, telling the experiment of the use of electricity, and drawing pictures of saving the fossil oil. The analysis and communication are done by students to analyze the result of the experiment. The communication activity was done both in individuals and the group.